Review of orchestra musicians’ hearing loss riskss - Eaton, Stuart; Gillis, Heather (Canadian Acoustics, 2002)
The noise exposure and hearing loss of symphony orchestra musicians were reviewed and the data on 53 members of the Vancouver Symphony Orchestra (VSO) was reported. The VSO data indicated high-frequency notches suggesting minimal noise damage in some musicians. Results showed asymmetries in hearing for violinists and flutists which could be attributed to asymmetrical sound exposure.